FUNDAMENTOS DE LA EDUCACIÓN MATEMÁTICA Y SU INCIDENCIA EN EL APRENDIZAJE DE CINEMÁTICA EN LOS ESTUDIANTES DE SEGUNDO AÑO DE BACHILLERATO GENERAL UNIFICADO. PARALELO “B” DE LA UNIDAD EDUCATIVA CARLOS CISNEROS EN EL PERIODO LECTIVO SEPTIEMBRE 2019-FEBRERO 2020. - Bone Salas, Javier Alejandro (2020)
This research intended to find a solution to a worldwide common problem: the lack of mathematical basics students need to achieve a proper learning process of Physics, particularly, Kinematics. It’s no secret that Mathematics are one of the hardest-to-learn subjects for students of any level due to several factors, from which only a few (most necessary ones) have been used in this research. The main goal in this research was to analyze how the basics of mathematical education incide in the learning of Kinematics. This is quantitative field research, at a descriptive level of transversal, non-experimental design. The research’s population is represented by unified second grade students from Carlos Cisneros High School, September 2019-February 2020, belonging to Class Section B. Aptitude Test was used for data collection. Test results show all students do not possess Mathematics basics required for the resolution of Kinematics problems.